Maslinic acid prevents IL‐1β‐induced inflammatory response in osteoarthritis via PI3K/AKT/NF‐κB pathways - Chen, Yan‐Lin; Yan, De‐Yi; Wu, Chen‐Yu; Xuan, Jiang‐Wei; Jin, Chen‐Qiang; Hu, Xin‐Li; Bao, Guo‐Dong; Bian, Yu‐Jie; Hu, Zhi‐Chao; Shen, Zhong‐Hai; Ni, Wen‐Fei (Journal of cellular physiology, 2021)
Osteoarthritis (OA) is a degenerative joint disease characterized by destruction of articular cartilage. The inflammatory response is the most important factor affecting the disease process. As interleukin‐1β (IL‐1β) stimulates several key mediators in the inflammatory response, it plays a major role in the pathogenesis of OA. Maslinic acid (MA) is a natural compound distributed in olive fruit. Previous studies have found that maslinic acid has an inhibitory effect on inflammation, but its specific role in the progression of OA disease has not been studied so far. In this study, we aim to assess the protective effect of MA on OA progression by in vitro and in vivo experiments. Our results indicate that, in IL‐1β‐induced inflammatory response, MA is effective in attenuating some major inflammatory mediators such as nitric oxide (NO) and prostaglandin E2, and inhibits the expression of IL‐6, inducible nitric oxide synthase, cyclooxygenase‐2, and tumor necrosis factor‐α (TNF‐α) in a concentration‐dependent manner. Also, MA downregulated the expression levels of thrombospondin motif 5 (ADAMTS5) and matrix metalloproteinase 13 in chondrocytes, resulting in reduced degradation of its extracellular matrix. Mechanistically, MA exhibits an anti‐inflammatory effect by inactivating the PI3K/AKT/NF‐κB pathway. In vivo, the protective effect of MA on OA development can be detected in a surgically induced mouse OA model. In summary, these findings suggest that MA can be used as a safe and effective potential OA therapeutic strategy. Maslinic acid (MA) could prevent IL‐1β‐associated inflammation as well as extracellular matrix (ECM) degradation in human osteoarthritis (OA) chondrocytes. The potential mechanism involved in the protective effect of MA was that it could reverse inflammation‐related destruction via inhibiting PI3K/AKT/NF‐κB pathways activation. MA ameliorates OA progression in vivo via inhibiting the devastation of cartilage surface, cartilage calcification, and osteophytes formation.